The Role of Candida albicans Transcription Factor RLM1 in Response to Carbon Adaptation - Oliveira-Pacheco, João; Alves, Rosana; Costa-Barbosa, Augusto; Cerqueira-Rodrigues, Bruno; Pereira-Silva, Patricia; Paiva, Sandra; Silva, Sónia; Henriques, Mariana; Pais, Célia; Sampaio, Paula (Frontiers in Microbiology, 2018)
Candida albicans is the main causative agent of candidiasis and one of the most frequent causes of nosocomial infections worldwide. In order to establish an infection, this pathogen supports effective stress responses to counter host defenses and adapts to changes in the availability of important nutrients, such as alternative carbon sources. These stress responses have clear implications on the composition and structure of Candida cell wall. Therefore, we studied the impact of lactate, a physiologically relevant carbon source, on the activity of C. albicans RLM1 transcriptional factor. RLM1 is involved in the cell wall integrity pathway and plays an important role in regulating the flow of carbohydrates into cell wall biosynthesis pathways. The role of C. albicans RLM1 in response to lactate adaptation was assessed in respect to several virulence factors, such as the ability to grow under cell wall damaging agents, filament, adhere or form biofilm, as well as to immune recognition. The data showed that growth of C. albicans cells in the presence of lactate induces the secretion of tartaric acid, which has the potential to modulate the TCA cycle on both the yeast and host cells. In addition, we found that adaptation of C. albicans cells to lactate reduces their internalization by immune cells and consequent % of killing, which could be correlated with a lower exposure of the cell wall ß-glucans. In addition, absence of RLM1 has a minor impact on internalization, compared with the wild-type and complemented strains, but it reduces the higher efficiency of lactate grown cells at damaging phagocytic cells and induces a high amount of IL-10, rendering these cells more tolerable to the immune system. The data suggests that RLM1 mediates cell wall remodeling during carbon adaptation, impacting their interaction with immune cells.